The Relationship of Early Childhood Education Teachers' Knowledge of Children's Rights to Protection with Prevention of Verbal Violence - Ulani, Reni Sri; Latiana, Lita (BELIA: Early Childhood Education Papers, 2019)
Implementation of children's rights to protection, especially in schools can be realized, if there is a role from teachers. One of the most important and fundamental roles of teachers is the knowledge of teachers about the rights of child protection. Child Protection Law number 35 of 2014 states that the protection of children in schools is conducted one of them by the teacher. This study aims to find out the knowledge of PAUD teachers of children's rights to protection and their relationship with the prevention of verbal violence in TK ABA Temanggung District. The research method used is quantitative correlational, and data collection techniques using a questionnaire. The population is 76 teachers in TK ABA Temanggung District. The sampling is done by Simple Random Sampling (randomly) totalling 30 teachers. The data analysis in this study uses product-moment correlation analysis. The results show that teachers' knowledge of children's rights to protection at the low level is 10 teachers (33.3%), the moderate level is 17 teachers (56.7%), and at the high level only 3 teachers (10.0%). The results of the product-moment correlation analysis obtain a significance value of 0,000. The significance value < 0.05 means that the PAUD teacher's knowledge variable about children's rights to protection by preventing verbal violence in TK ABA in Temanggung District correlates. While the Pearson correlation value of 0.838, when viewed in the guidelines table to provide an interpretation of the correlation coefficient Pearson correlation values are in the coefficient interval of 0.80-1,000. It can be concluded that most of the teacher's knowledge about child protection rights is at the mid-level. There is a positive and very strong relationship between PAUD teachers' knowledge about children's protection rights and the prevention of verbal violence in TK ABA Temanggung District.